Prokaryotic carbon utilization in the dark ocean: growth efficiency, leucine-to-carbon conversion factors, and their relation - Baltar, Federico; Arístegui, Javier; Gasol, Josep M.; Herndl, Gerhard J. (Aquatic Microbial Ecology, 2010)
6 pages, 2 figures, 3 tables Experiments were conducted in the mesopelagic subtropical northeast Atlantic Ocean to determine the range of variability in the prokaryotic leucine-to-carbon conversion factor (CF), and prokaryotic growth efficiency (PGE). The way prokaryotic heterotrophic production (PHP) is calculated directly influences PGE (variations of PGE between 1 and 31% were found for a single sample). The empirically obtained deep-water CFs showed a 7-fold variability (0.13 to 0.85 kg C mol-1 Leu), but were always lower than the theoretical CF of 1.55 kg C mol-1 Leu assuming no isotope dilution. Empirically determined CFs were highly correlated to PGE, suggesting that both parameters are representations of the same basic metabolic processes. Overall, the PGEs obtained in this study suggest that mesopelagic prokaryotic assemblages can sometimes be as important in carbon processing as their epipelagic counterparts This research was supported by the Spanish ‘Plan Nacional de I+D’ (MEC) under the RODA (CTM2004-06842-C03-03/MAR) and CAIBEX (CTM2007-66408-C02-02) grants to J.A., a grant of the Earth and Life Science Division of the Dutch Science Foundation (ALW-NWO; ARCHIMEDES project, 835.20.023) to G.J.H., and a predoctoral Fellowship of the Spanish Ministry of Education and Science (AP2005-3932) to F.B. Projects MODIVUS (CTM2005-04795/ MAR) and STORM (CTM2009-09352/MAR) supported J.M.G. The work was carried out within the frame of the EU ‘Networks of Excellence’ MarBef, and EurOceans Peer Reviewed